Infective spondylodiscitis in patients on maintenance hemodialysis: a case series. (1st January 2017) - Lu, Yueh-An; Hsu, Hsiang-Hao; Kao, Huang-Kai; Lee, Chia-Hui; Lee, Shen-Yang; Chen, Guan-Hsing; Hung, Cheng-Chieh; Tian, Ya-Chung
Abstract: Infective spondylodiscitis is a rare disease. This case review describes the clinical course, risk factors, and outcomes of adult patients on maintenance hemodialysis who presented with infective spondylodiscitis at a single medical center in Taiwan. There were 18 cases (mean age: 64.9 ± 10.8 years) over more than 10 years. Analysis of underlying diseases indicated that 50% of patients had diabetes, 55.6% had hypertension, 55.6% had coronary artery disease, 22.2% had congestive heart failure, 22.2% had a cerebral vascular accident, 16.7% had liver cirrhosis, and 11.1% had malignancies. Sixty-one percent of patients had a degenerative spinal disease and the most common symptom was back pain (83.3%). A total of 38.9% of patients had leukocytosis, 99.4% had elevated levels of C-reactive protein, 78.6% had elevated erythrocyte sedimentation rates, and 55.6% had elevated levels of alkaline phosphatase. The average hemodialysis duration was 72.8 ± 87.5 months, and 8 patients (44.4%) started hemodialysis within 1 year prior to infective spondylodiscitis. Four patients (22.2%) had vascular access infection-associated spondylodiscitis. The lumbar region was the most common location of infection (77.8%), 44.4% of patients developed abscesses, and Staphylococci were the most common pathogen (38.9%). The mortality rate was 16.7%, all due to sepsis. Thirty-three percent of the survivors had recurrent infective spondylodiscitis within 1 year. Infective spondylodiscitis should be considered in hemodialysis patients who present with prolonged back pain with or without fever. Non-contrast MRI is an appropriate diagnostic tool for this condition. Vascular access infection increases the risk for infective spondylodiscitis in hemodialysis patients.